Pengaruh Jumlah Penduduk, Pengangguran, Pengeluaran Perkapita, Indeks Pembangunan Manusia dan Pertumbuhan Ekonomi Terhadap Tingkat Kemiskinan (Studi Kasus 3 Kabupaten di Provinsi Kalimantan Selatan) - Nanda, Rekha; Fahrati, Eny (PPJP ULM, 2023)
This study aimed to determine the effect of population, unemployment, per capita expenditure, human development index, and economic growth on poverty levels in Banjar, Tapin, and Hulu Sungai Tengah districts. As secondary data, panel data from the Central Statistics Agency (BPS) of South Kalimantan Province is used in this quantitative descriptive analysis. The data analysis technique was used in the panel data regression method. In Banjar, Tapin, and Hulu Sungai Tengah districts, the poverty rate is influenced by population, open unemployment, underemployment, per capita expenditure, human development index, and economic growth. Population negatively and significantly affects poverty rates in Banjar, Tapin, and Hulu Sungai Tengah regencies. In contrast, open unemployment has a negative and insignificant impact, underemployment has a positive and significant impact, and expenditure per capita has a positive and significant impact. The human development index has a positive and considerable influence, and economic growth has a positive and insignificant effect.